The economic and clinical burden of nonalcoholic fatty liver disease in the United States and Europe. Issue 5 (26th September 2016) - Younossi, Zobair M.; Blissett, Deirdre; Blissett, Robert; Henry, Linda; Stepanova, Maria; Younossi, Youssef; Racila, Andrei; Hunt, Sharon; Beckerman, Rachel
Abstract : Nonalcoholic fatty liver disease (NAFLD) is a major cause of chronic liver disease. There is uncertainty around the economic burden of NAFLD. We constructed a steady‐state prevalence model to quantify this burden in the United States and Europe. Five models were constructed to estimate the burden of NAFLD in the United States and four European countries. Models were built using a series of interlinked Markov chains, each representing age increments of the NAFLD and the general populations. Incidence and remission rates were calculated by calibrating against real‐world prevalence rates. The data were validated using a computerized disease model called DisMod II. NAFLD patients transitioned between nine health states (nonalcoholic fatty liver, nonalcoholic steatohepatitis [NASH], NASH‐fibrosis, NASH‐compensated cirrhosis, NASH‐decompensated cirrhosis, hepatocellular carcinoma, liver transplantation, post‐liver transplant, and death). Transition probabilities were sourced from the literature and calibrated against real‐world data. Utilities were obtained from NAFLD patients using the Short Form‐6D. Costs were sourced from the literature and local fee schedules. In the United States, over 64 million people are projected to have NAFLD, with annual direct medical costs of about $103 billion ($1, 613 per patient). In the Europe‐4 countries (Germany, France, Italy, and United Kingdom), there are ∼52 million people with NAFLD with an annual cost of about €35 billion (from €354 to €1, 163 per patient). Costs are highest in patients aged 45‐65. The burden is significantly higher when societal costs are included. Conclusion: The analysis quantifies the enormity of the clinical and economic burdens of NAFLD, which will likely increase as the incidence of NAFLD continues to rise. (Hepatology 2016;64:1577‐1586)